Status Pengelolaan Perikanan Cakalang di Kabupaten Wakatobi Berdasarkan Indikator Domain Teknik Penangkapan Ikan Pengelolaan Perikanan Berpendekatan Ekosistem - Wildayanti Wildayanti; Naslina Alimina; Ahmad Mustafa; Muslim Tadjuddah; Syamsul Kamri (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2022)
Wakatobi Waters are part of the Fishery Management Area (WPP) 714 which has potential resources for large pelagic fish including skipjack tuna (Katsuwonus pelamis). The purpose of this study was to determine the management status of the skipjack tuna fishery in Wakatobi District based on the fishing technique domain indicators set by the EAFM National Working Group. The research was carried out from October to December 2021 using a survey method, through interviews with questionnaires to stakeholders and literature studies. Data analysis uses the scoring method and the flag model. The results showed that indicators of destructive and/or illegal fishing methods indicated that >10 violations per years occurred but were not related to skipjack fisheries. The indicator of modification of fishing gear and fishing aids shows more than 50% of the size of the target fish produced < Lm. Fisheries capacity and fishing effort indicators show an average fishing capacity ratio in 2019 and 2021 of 1.47. The fishing selectivity indicator shows that 100% of the fishing gear used is classified as selective fishing gear. Indicators of suitability of the function and size of fishing vessels with legal documents show that all Tho line fishing vessels do not have legal documents. The results of the composite analysis of all indicators of the fishing technique domain yield a value of 220 which is classified as in good condition.